CONSUMER BEHAVIOR IN DECISION-MAKING ON PALM SUGAR PRODUCT ATTRIBUTES - Albafery, Albafery; Darimi, Darimi (Komunitas Manajemen Kompetitif, 2024)
Consumer behavior encompasses actions directly involved in acquiring, consuming, and disposing of products or services, including the processes that occur before and after these actions. Palm sugar, which is used both as a sweetener and in herbal medicine, affects consumer behavior in unique ways. This study aims to explore consumer behavior in decision-making, focusing on the attributes of palm sugar products. Conducted in Rambah Tengah Barat Village, Rambah District, the study utilizes the Fishbein model for data analysis. The findings show that consumer behavior is generally positive, with product taste being the most influential factor in decision-making.